2021
DOI: 10.1016/j.cbi.2021.109449
|View full text |Cite
|
Sign up to set email alerts
|

Role of phytoconstituents in the management of COVID-19

Abstract: Background COVID-19, a severe global pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) has emerged as one of the most threatening transmissible disease. As a great threat to global public health, the development of treatment options has become vital, and a rush to find a cure has mobilized researchers globally from all areas. Scope and approach This review focuses on deciphering the potential of different secondary metabolites from medicina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 173 publications
0
44
0
1
Order By: Relevance
“…Considering this pervasive situation, it is essential to apply different strategies to tackle the present scenario. The plants with medicinal properties have provided an excellent and widespread therapeutic alternative since ancient times against various infectious diseases owing to their safer, cheaper, and less toxicity profile [29] , [30] , [31] , [32] , [33] . Phytoconstituents are important compounds for drug discovery against various human diseases [34] , [35] , [36] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering this pervasive situation, it is essential to apply different strategies to tackle the present scenario. The plants with medicinal properties have provided an excellent and widespread therapeutic alternative since ancient times against various infectious diseases owing to their safer, cheaper, and less toxicity profile [29] , [30] , [31] , [32] , [33] . Phytoconstituents are important compounds for drug discovery against various human diseases [34] , [35] , [36] .…”
Section: Introductionmentioning
confidence: 99%
“…These polyphenolic compounds, alkaloids, comprise multiple essential characteristics against viral diseases like immune system alteration [50] , suppression of viral replication [51] , and decrease in viral uptake by host target membrane [52] . Moreover, studies have suggested the anti-viral activity of phytoconstituents against rabies virus, HIV, chandipura virus, Japanese Encephalitis Virus, Enterovirus, Influenza A/H1N1, other influenza viruses, and SARS-CoV-2 [30] , [53] , [54] , [55] . Phytoconstituents show beneficial impact on COVID-19 therapy are listed in Table 2 , and their sites of action are illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
“… The fixed oil and thymoquinone both found to down-regulate COX, 5-LO, 5-HETE and suppresses IL-6, TNFα, and NO production The aqueous seed extract improves both cellular immunity and humoral immunity by stimulating CD4+ Salim and Noureddine, 2020 ; Kakepoto, 2020; Majdalawieh and Fayyad, 2015 Solanaceae Withania somnifera (L.) Dunal Withanone (xviii) block or weaken COVID-19 entry and its subsequent infectivity Steroidal lactones and quercetin potentially inhibited SARS COV PLpro and 3CLpro Aqueous root extract inhibited IL -8, IL‑6, TNF‑α, IL‑1β and IL‑12 A herbo mineral formulation containing aswagandha significantly increased the CD4+ and CD8+. Balkrishna et al, 2020b ; Gupta et al, 2014; Chandra et al, 2012 ; Sikandan et al, 2018 ; Leemol Davis and Girija Kuttan, 2000; Gupta et al, 2006 ; Trivedi et al, 2017 ; Das et al, 2021 Taxaceae Torreya nucifera (L.) Siebold & Zucc. Biflavone (xix), amentoflavone (xx) showed 3CLpro inhibitory effect The leaves reduced secretion of IL-1β, IL-6, NO and PGE2 Ryu et al, 2010 a; Yoon et al, 2009 Theaceae Camellia sinensis (L.) Kuntze Theaflavin-3’-gallate, Theaflavin-3,3’-digallate and tannic acid are effective against 3CLPro Isolated Theaflavin from leaves of C. sinensis exhibited inhibitory activity against SARS-COV-2 virus through binding to RNA dependent RNA polymerase Ethanol leaf extract and epigallocatechin gallate suppressed the production of NO, COX-2, IL-6, IL-1β, and TNF-α Hot water extract of leaves significantly increased blood leucocyte, lymphocyte count, peritoneal macrophages, spleen and thymic lymphocytes count, lung macrophages count Chen et al, 2005 ; Novilla et al, 2017 ; Gomes et al, 2013; Sharangi, 2009 ; Islam et al, 2021 Zingiberaceae Zingiber officinale Roscoe 6-gingerol (xvii) showed interaction with viral proteases, RNA binding protein, Spike protein Hot water extracts of fresh rhizomes inhibited viral attachment of human respiratory syncytial virus (HRSV) Rhizome supplement reduced TNF-α, IL-6 level.…”
Section: Herbal Formulae From Different Traditional Systems Of Medicinementioning
confidence: 99%
“…A maior parte dos trabalhos incluídos nestas áreas, investigam o progresso do potencial medicinal e terapêutico de plantas como antiviral e anti-inflamatório, na prevenção e tratamento da COVID-19 (Shin, Oh & Jeong, 2021;Prasansuklab et al, 2021;Lu et al, 2021;Das et al, 2021). Esses dois fatores, antiviral e anti-inflamatório, combinados, são relevantes e necessários para a produção de novos medicamentos para o tratamento eficiente da COVID-19 (Shin, Oh & Jeong, 2021) e a quercetina estaria inclusa nestes estudos.…”
Section: Prospecção Científicaunclassified